1990
DOI: 10.1038/cr.1990.9
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of calmodulin and Ca2+-activated calmodulin in cell cycle of mouse erythroleukemia cells

Abstract: The activation of the heme oxygenase (HO), fos, and AP-1 genes was determined at intervals after treatment of M1 cells (derived from mouse myeloleukemia) with heme or 12-O-tetradecanoylphorbol 13-acetate (TPA). On treatment with heme, M1 cells did not differentiate into macrophage but their HO gene was activated and showed maximum transcriptional activity after treatment with heme for 2 h. In contrast, on treatment with TPA, these cells adhered to the culture flasks within 5 h and differentiated into macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
1995
1995

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Considering phenothiazine drugs could only give the information of Ca 2+ -activated CaM site and may be not completely specific to CaM [17], we further determined the distribution of total CaM in tip growing hyphae by immunohistochemical method, which could be used for the localization of both inactivated and Ca 2+ -activated CaM sites [18]. Thus, a gradient of brownish reaction product from tip to base in hyphal tips was observed (Fig 4, 5), revealing the concentration of total CaM mainly in the apex of hyphae.…”
Section: Discussionmentioning
confidence: 99%
“…Considering phenothiazine drugs could only give the information of Ca 2+ -activated CaM site and may be not completely specific to CaM [17], we further determined the distribution of total CaM in tip growing hyphae by immunohistochemical method, which could be used for the localization of both inactivated and Ca 2+ -activated CaM sites [18]. Thus, a gradient of brownish reaction product from tip to base in hyphal tips was observed (Fig 4, 5), revealing the concentration of total CaM mainly in the apex of hyphae.…”
Section: Discussionmentioning
confidence: 99%
“…Neither results were based on individual cell study, We have demonstrated that intracellular CaM level was increased from G1 through S to G2M [6], Although there was a report that total protein was increased along the cell cycle too [7],it is unclear whether the increase of intracellular level of CaM represented a true increase in the total intracellular level of this protein. The present work was undertaken in order to determine whether the rise of specific activity actually represents an increase of CaM molecules per cell based on the ratio of CaM to protein in individual cells and whether such change denotes a more general response to transformation by oncogenic viruses and irradiation as well.…”
Section: Introductionmentioning
confidence: 91%